Learning recommendation with formal concept analysis for intelligent tutoring system - Muangprathub, Jirapond; Boonjing, Veera; Chamnongthai, Kosin (My University, 2020)
Computer Science; Learning recommendation; Formal concept analysis; Intelligent tutoring system; Adaptive learning
Keywords: Adaptive learning; Computer Science; Formal concept analysis; Intelligent tutoring system; Learning recommendation